Effect of deposition time on gold nanodendrite porous structure and on signals of Hg(II) in environment - Hai Yen, Pham Thi; Dang, Vu Hai; Anh, Nguyen Hoang; Thu Ha, Vu Thi (Vietnam Journal of Chemistry, 2017)
The influences of deposition time (tdep) for Au nanodendrite preparation on carbon cloth electrodes on the surface structure, electrochemical behavior and voltammetric signal for Hg(II) detection have been studied. The obtained results showed that from 60 s to 300 s, the longer deposition time, the larger dendrite length as well as the more increased density of dendrite structure became. Calculated from data showed that the electroactive surface area approached to the maximum value of 3.686 cm2 with tdep = 300 s. The typical electrochemical behaviour of the prepared electrodes was mass transfer diffusion to the electrode surface and being considered as planar diffusion. Using DPASV technique, the peak height of Hg(II) could appoach to 52 µA with tdep = 60 s. Keywords. Gold nanodendrite, deposition time, surface structure, electrochemical properties, mercury.